Are lemons sold first? Dynamic signaling in the mortgage market - Manuel Adelino; Kristopher Gerardi; Barney Hartman-Glaser (Federal Reserve Bank of Atlanta, 2016)
A central result in the theory of adverse selection in asset markets is that informed sellers can signal quality by delaying trade. This paper uses the residential mortgage market as a laboratory to test this mechanism. Using detailed, loan-level data on privately securitized mortgages, we find a strong relation between mortgage performance and time-to-sale. Importantly, this finding is conditional on all observable information about the loans. This effect is strongest in the "Alt-A" segment of the market, where loans are often originated with incomplete documentation. The results provide some of the first evidence of a signaling mechanism through delay of trade.
Keywords: G17; G21; G23; 330; securitization; mortgage default; adverse selection; signaling; asymmetric information